PENGARUH LIABILITAS JANGKA PENDEK DAN LIABILITAS JANGKA PANJANG TERHADAP TINGKAT PROFITABILITAS PADA PT. INDOSPARING Tbk. PERIODE 2021-2024 - Eli Samali; Loransya, Yusiaris Dores (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research is motivated by globalization and business competition, liabilities being an important external source of funds but also bringing financial physics, and data from 2021- 2024 showing fluctuations in liabilities and profits, indicating a complex relationship between the two. Therefore, this study aims to determine the effect of short-term and long-term liabilities on the profitability of PT Indospring Tbk. This research was conducted on the Indonesia Stock Exchange from March to April 2025. The research method used is quantitative. The data used is secondary data obtained from PT Indospring Tbk's financial statements for 2021-2024. The analytical techniques used are debt and profitability ratios, multiple regression, t-tests, F-tests, and coefficients of determination. The results show a complex correlation between liabilities and profitability. Increases in liabilities are not always followed by increases in profitability, and vice versa. 2023 proves that with proper management, companies can generate large profits despite their significant debt ratios. This study recommends that companies increase the use of liabilities that support productive activities to generate profit in order to maintain a competitive ROE above industry standards